Development and validation of the Perceived Influences on Sport and Study Assessment Scale - Larissa Fernanda Porto Maciel; Mônica Cristina Flach; William das Neves Salles; Ricardo Teixeira Quinaud; Juarez Vieira do Nascimento; Alexandra Folle (Avaliação Psicológica, 2021)
The objective of this cross-sectional study was to develop and validate an Assessment Scale for Perceived Influences in Sport and Study (EIPE). The validation process was carried out with specialists and athletes of both sexes, from team and individual sports, aged between 13 and 18 years old and who attended secondary and high school Education in Santa Catarina/Brazil. Five steps were taken in order to validate the instrument: content validity; clarity of language; pilot test; construct validity; internal consistency; and reliability. Results showed that the final version of the EIPE (two factors and 49 items) showed satisfactory adjustment indices (χ2/gl = 1.751; GFI = .85; AGFI = .82; CFI = .90; SRMR = .059; RMR = .046; RMSEA = .042; CFI = .90; TLI = .89), high internal consistency (α > .70) and reliability (α > .91). It is concluded that the EIPE has satisfactory psychometric properties that provide evidence of scientific validity and reliability.